Diseminasi Teknologi Produksi Agens Hayati sebagai Solusi Alternatif dalam Produktivitas Buah Naga: Indonesia - Siti Asmaul Mustaniroh; Sunyoto, Nimas Mayang Sabrina; Yulianingsih, Rini; Zahro, Frelyta Ainuz; Andriani, Ria Dewi; Kirana, Wahyu Candra (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Banyuwangi Regency, a major dragon fruit producer in Indonesia, has a cultivation area of 3,786 hectares and an annual production of 82,544 tons in 2020, up from 19,068 tons in 2019. Despite the use of Ultraviolet (UV) light technology increasing productivity to 2,350 tons per hectare in Sarongan village, there has been a drastic 60% drop in production over the past two years. This decline is accompanied by plant health issues and high costs for pesticides and chemical fertilizers, highlighting the need for more efficient solutions. The use of biological agents, relying on natural enemies to control pests and diseases, offers a sustainable solution. Microbes and fungi can reduce reliance on chemical pesticides and improve plant health. This study evaluates the application of biological agents through technical guidance, using potato broth for Beauveria bassiana and Trichoderma sp., and soybean broth for Azotobacter sp. and Pseudomonas fluorescens. Testing results show that Azotobacter sp. and Pseudomonas fluorescens have adequate populations and are effective in enhancing soil health and plant productivity. The use of nutrient-rich media such as potato broth improves the growth of Beauveria bassiana and Trichoderma sp. Field application of biological agents resulted in a 30% increase in harvest yield, reduced dependence on chemical pesticides, and lowered production costs. Practical recommendations include using optimal nutrient media, farmer training, and regular monitoring and evaluation to enhance effectiveness and sustainability. This technology is expected to support sustainable agriculture and significantly boost dragon fruit productivity.